Design and Implementation of Wireless Digital Energy Meter using Microcontroller (Global Journals of Research in Engineering, 2012)
This paper presents a micro-controller based wireless digital energy meter to facilitate energy consumption measurement and its corresponding billing scheme. Details of design for the construction of energy meter using (Current transformer, Potential transformer, microcontroller, Atmega 16, LCD, Transmitter, Receiver, and a load). Electricity has become one of the basic requirements of human civilization, being widely used for domestic, industrial and agricultural purposes. At present, the need and demand for electricity requires no special mention. In spite of very well developed sources for electricity, both traditional and alternate versions, there are a lot of problems with distribution, metering and billing of electrical energy and its consumption measurement. The problem worsens further in collecting the meter readings and generating the bill. In this paper, a method of using a wireless digital system for automated transmission of data was utilized to make easy energy consumption measurement and its consequent billing system. If we use this energy meter it will be beneficial for the power energy system. It is very cost effective and effortless to operate.
Keywords: Current transformer; Potential transformer; microcontroller (Atmega 16); LCD; Transmitter; Receiver